2012
DOI: 10.3748/wjg.v18.i19.2295
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and health-related quality of life

Abstract: Hepatitis C virus (HCV) hepatitis and other diseases related to HCV, such as cryoglobulinemia, lymphoma and renal failure, impair health-related quality of life (HRQoL). In addition, HCV per se might directly influence HRQoL via colonization of microglia in the brain or, indirectly, via the effect of systemic inflammatory cytokines which, in turn, can trigger brain interleukin production. The treatment of HCV-related disorders with interferon (IFN) has an effect on HRQoL. Initially, IFN causes a transient dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
1
25
1
Order By: Relevance
“…This poorer outcome with HCV compared to HBV is consistent with previous studies,[171836] though Weinstein et al .,[36] found one of the independent predictors of depression to be female gender, in contrast to our observations. That HRQoL scores previously observed in an SF-36 questionnaire were reduced in HCV, but not HBV infection,[37] signifies that HCV infection per se reduces HRQoL rather than producing a non-specific awareness of having a viral infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This poorer outcome with HCV compared to HBV is consistent with previous studies,[171836] though Weinstein et al .,[36] found one of the independent predictors of depression to be female gender, in contrast to our observations. That HRQoL scores previously observed in an SF-36 questionnaire were reduced in HCV, but not HBV infection,[37] signifies that HCV infection per se reduces HRQoL rather than producing a non-specific awareness of having a viral infection.…”
Section: Discussionsupporting
confidence: 93%
“…One study investigating the incidence of psychiatric illness in patients infected with either HCV or HBV reported a higher incidence of major depressive disorder in hepatitis C patients than in controls or those infected with hepatitis B. [17] Moreover, health-related quality of life (HRQoL) has been shown to be unrelated to severity of liver disease in HCV infection,[18] suggesting a pathophysiological link between HCV and depression.…”
mentioning
confidence: 99%
“…The results confirmed that psychiatric co-morbidity is associated with HCV infection independent of substance use and alcohol disorders. While others have previously found such an association (Amodio et al, 2012;Butt et al, 2006;Dominitz et al, 2005;Nelligan et al, 2008;Osher et al, 2003), our study demonstrated this in a large inner city substance misuse population. Although the difference is small, the results suggest that the prevalence of HCV infection is high in both groups and therefore HCV infection is a considerable problem.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition to the impact of treatment, several other factors affect HRQOL in HCV-infected patients. Several studies have found that a part of the reduction in HRQOL can be explained by substance addiction, cirrhosis, and other comorbidities (8). However, there is a strong line of evidence that HRQOL is impaired in HCV patients even when these factors are controlled (9-11).…”
Section: Resultsmentioning
confidence: 99%